IMPROVING WRITING SHORT STORY SKILL BASED ON FOLKLORE BY USING THINK TALK WRITE METHOD - Nursitawati, Erlina Firsty; Sumarwati, Sumarwati; Rohmadi, Muhammad (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2017)
Writing is a skill about pouring an idea or concept in form of write (written). The research which is done in X IPA 2 class of SMA Negeri Karangpandan showed that the value of the student writing skill is still low. This research purpose is to raise a writing skill of the learners which is use a Think Talk Write method. This research is held on March until May. The subjects in this research are the teachers and the student of X IPA 2 class in SMA Negeri Karangpandan. The data is in the form of picture, video, Education of Implementation plan, test result, list of value, transcription of interviewing and field record. The resource of the data include: Informant, Place and Event, and the document. The data validity uses a triangulation method and triangulation data resource. The analysis data technique is use analysis critical technique and descriptive comparative technique. The indicator achievement amount 80% .The research procedure comprise with planning, implementation of the action, and reporting. The Result from this research showed that the application of Think Talk Write method could raise a writing skill based on folklore student of X IPA 2 class in SMA Negeri Karangpandan.Key words: writing short story, folklore, Think Talk Write methodPENINGKATAN KETERAMPILAN MENULIS CERPEN BERDASARKAN CERITA RAKYAT MENGGUNAKAN METODE THINK TALK WRITEAbstrakMenulis merupakan suatu keterampilan dalam menuangkan ide atau gagasan dalam bentuk tulis. Penelitian yang dilakukan di kelas X IPA 2 SMA Negeri Karangpandan menunjukkan bahwa masih rendahnya nilai keterampilan siswadalam menulis. Penelitian ini bertujuan untuk meningkatkan keterampilan menulis peserta didik dengan menggunakan metode Think Talk Write. Penelitian ini dilaksanakan pada bulan Maret sampai bulan Mei. Subjek dalam penelitian ini adalah guru dan peserta didik kelas X IPA 2 SMA Negeri Karangpandan. Data berupa foto, video, rpp, hasil tes, daftar nilai, catatan hasil wawancara dan catatan lapangan. Sumber data meliputi: informan, tempat dan peristiwa, dan dokumen. Keabsahan data menggunakan triangulasi metode dan triangulasi sumber data. Teknik analisis data dengan teknik analisis kritis dan teknik deskriptif komparatif. Indikator ketercapaian sebesar 80%. Prosedur penelitian terdiri perencanaan, pelaksanaan tindakan, dan pelaporan. Hasil dari penelitian menunjukkan bahwa penerapan metode Think Talk Write mampu meningkatkan keterampilan menulis cerpen berdasarkan cerita rakyat peserta didik kelas X IPA 2 SMA Negeri Karangpandan.Kata Kunci: menulis cerpen, cerita rakyat, metode Think Talk Write